2013
DOI: 10.1038/nature11799
|View full text |Cite
|
Sign up to set email alerts
|

Studying arrhythmogenic right ventricular dysplasia with patient-specific iPSCs

Abstract: Cellular reprogramming of somatic cells to patient-specific induced pluripotent stem cells (iPSCs) enables in-vitro modelling of human genetic disorders for pathogenic investigations and therapeutic screens1–7. However, using iPSC-derived cardiomyocytes (iPSC-CMs) to model an adult-onset heart disease remains challenging due to the uncertainty regarding the ability of relatively immature iPSC-CMs to fully recapitulate adult disease phenotypes. Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
424
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(443 citation statements)
references
References 35 publications
13
424
1
5
Order By: Relevance
“…Although the fatty infiltration was not extensive in iASPP Δ8/Δ8 hearts, it was undetectable in wild-type controls. Recently it has been suggested that PPARγ activation is important in adipogenesis and ARVC pathogenesis (38). We observed a clear increase in the protein levels of PPARγ and its target gene adiponectin in hearts from iASPP-deficient mice compared with wild-type control hearts (Fig.…”
Section: Loss Of Iaspp Increases Desmoplakin Phosphorylation and Solusupporting
confidence: 54%
See 1 more Smart Citation
“…Although the fatty infiltration was not extensive in iASPP Δ8/Δ8 hearts, it was undetectable in wild-type controls. Recently it has been suggested that PPARγ activation is important in adipogenesis and ARVC pathogenesis (38). We observed a clear increase in the protein levels of PPARγ and its target gene adiponectin in hearts from iASPP-deficient mice compared with wild-type control hearts (Fig.…”
Section: Loss Of Iaspp Increases Desmoplakin Phosphorylation and Solusupporting
confidence: 54%
“…S6B). PPARγ signaling previously has been implicated in adipogenesis in ARVC (38,46), and its activation also was present in iASPP-deficient hearts (Fig. S6C).…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, the human heart is composed not only of CMs but also vascular, smooth muscle and epicardial cells; to better mimic its function, we predict that 3D cardiac tissue structures will be widely implemented, especially where interactions between different cell types might underlie the disease. As an example, ARVC has been modelled in hiPSC‐CMs and these are the major cellular players in the cardiac dysfunction in this disease 30, 34, 73; however, the suspected contribution of epicardial cells to fibro‐fatty substitution and the role of inflammation could not so far be studied in two‐dimensional monotypic cultures. The expectation is that complex multicellar structures will be necessary to reflect fully the pathology of the condition.…”
Section: Future Challengesmentioning
confidence: 99%
“…Generating 3D micro ECTs of variable cell compositions, using human-derived cardiac cells, has been demonstrated as discussed. Moreover, varying degrees of hPSC-CM maturation have been demonstrated by means of prolonged culture [26], topographical cues [14], electrical stimulation [14], mechanical stretching [19], and/or chemical manipulation [27], as well as coculture with cardiac fibroblasts [28] and endothelial cells [25]. Yet, there are currently no robust methods of promoting the functional maturation of hPSC-CMs within a short time frame.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Alternatively, 3D micro ECTs have been generated by seeding cardiac cells suspended in a hydrogel in a platform wherein they self-organize around a pair of posts (Figure 1(d, e)) [25]. The post platform both induces alignment within the 3D ECT (Figure 1(f)) due to the static stretch applied by the posts and provides a means of directly measuring the contractility of the ECT in situ.…”
Section: Three-dimensional Engineered Cardiac Tissues (Ects)mentioning
confidence: 99%